Analisis Kesalahan Penggunaan Kata “Chadianr” dan “Chabuduo” pada Mahasiswa Angkatan 2023 Prodi Pendidikan Bahasa Mandarin Universitas Tanjungpura - Uray Ridha Amalia; Tjen Veronica; Bun Yan Khiong (Publikasi Indonesia, 2026)
Vocabulary is a fundamental component in language learning because it plays a role as a basis for forming sentences and conveying meaning. In learning Chinese, the use of vocabulary that has similar meanings (synonyms) often causes errors, especially in the pairs of words